Analysis of The Utilization of Physics Laboratories in Several High Schools/Islamic Schools in Langkat Regency - Damayanti, Tia; Sinuraya, Jurubahasa (Current STEAM and Education Research, 2023)
This study aims to determine the condition of infrastructure facilities and the utilization of physics laboratories, to determine the utilization of physics laboratories, and to determine the inhibiting factors in the implementation of physics practicum activities in several SMA/MA in Langkat Regency. This type of research is an explorative survey, namely by observing and exploring (digging). Data collection was carried out through observation, surveys, interviews and documentation. The population in this study were all SMA/MA in Langkat Regency which had a physics laboratory. The sample in this study were 5 SMA/MA in Langkat Regency, namely Stabat 1 Public High School, Yapim Taruna Stabat Private High School, Padang Tualang 1 Public High School, Tanjung Pura 1 Public High School and Langkat 1 Public High School. Based on the results of data analysis, it was concluded that physics laboratories in several high schools/MA in Langkat Regency were classified as good with a percentage value of 70% according to Permendiknas No.24 of 2007. Laboratory utilization in general obtained a percentage value of 81% with a very good category. Inhibiting factors in the use of laboratories include insufficient time allocation, availability of practicum tools and materials, and the minimum number of laboratory assistants.